Peer Victimization and Adolescent Mental Health: School-level Victimization as a Moderator - Zhang, Yujie (Journal of interpersonal violence, 2024)
As a global issue, peer victimization is closely associated with adolescent mental health. Although previous research has explored the relationship between peer victimization and mental health in some contexts, the school context, particularly within the Chinese cultural context, has not received sufficient attention. Based on the Healthy Context Paradox, this study aimed to explore the moderating role of school-level victimization in the relationship between individual-level peer victimization and mental health. This study tested two hypotheses by using a multilevel design: higher individual-level and school-level peer victimization are associated with higher depressive symptoms and lower life satisfaction (Hypothesis 1); school-level victimization moderates the association between individual-level peer victimization and mental health (Hypothesis 2). Participants were 39,720 adolescents (50.41% females; Mage = 13.68, SD = 2.39) across 292 Chinese schools. They completed a set of questionnaires, including the Center for Epidemiologic Studies Depression Scale, the single-item Life Satisfaction Questionnaire, the Peer Victimization Scale, and demographics. The multilevel model indicated that both individual-level and school-level peer victimization were positively correlated with depressive symptoms and negatively correlated with life satisfaction. In schools with lower levels of victimization, there was a stronger association between individual peer victimization and adolescent mental health. A potential explanation for these results might be the victimization visibility and perceived severity in different contexts. These findings extended the discussion of the Healthy Context Paradox within the Chinese school context and provided valuable insights for developing school support strategies for victimized adolescents. School management might play a significant role in affecting the mental health of victimized adolescents.